Air pollution as a social and structural determinant of health - Lisa Patel (Elsevier, 2021)
Both short-term and chronic exposure to fine particulate matter air pollution (PM2.5) are known to cause a host of adverse health outcomes, including premature death. Exposure to PM2.5 in the United States is inequitable due to public policies rooted in structural racism, which have situated polluting industries intentionally in communities of color. Understanding variable exposure to PM2.5 is critical to understanding the disproportionate burden of chronic disease in US populations made vulnerable due to racism and poverty. This paper will review sources, health impacts and health inequities associated with PM2.5, and will frame PM2.5 as both a social and structural determinant of health. Based upon this framing, we will propose interventions that acknowledge individual counseling alone will be inadequate to protect our patients; community and policy level efforts to address structural determinants of health are needed.